Flexible piezoelectric polymer-based energy harvesting system for roadway applications - Jung, Inki; Shin, Youn-Hwan; Kim, Sangtae; Choi, Ji-young; Kang, Chong-Yun (ELSEVIER SCI LTD, 2017)
Interest in energy harvesters has grown rapidly over the last decade. The research effort in large-scale energy harvesting has mainly focused on piezoelectric ceramic based devices, due to its high piezoelectric constants. In this study, we demonstrate a piezoelectric energy harvester module based on polyvinylidene fluoride (PVDF) polymer for roadway applications. Flexible energy harvesters are fabricated with PVDF films and it exhibited stable performance and durability over the repeated number of bending cycles. In order to structurally optimize the design, finite element analysis was performed on two possible module configuration, with detailed input conditions on how the flexible energy harvester must be bent. A piezoelectric energy harvester module is then constructed with the fabricated unit energy harvesters inserted in the vertical direction, with initial radii of curvature as high as possible. The module was tested with a model mobile load system (MMLS3) and exhibited up to 200 mW instantaneous power output across a 40 k Omega resistor. The power output scaled linearly with the number of parallel connected harvesters. The calculated power density at this impedance reaches up to 8.9 W/m(2), suggesting that the flexible energy harvesters based on the piezoelectric polymers may provide energy density as high as those based on piezoelectric ceramics. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: CIRCUIT; FATIGUE; TEMPERATURE